PaeX, a Second Pectin Acetylesterase of Erwinia chrysanthemi 3937 - Shevchik, Vladimir E. (American Society for Microbiology, 2003)
Erwinia chrysanthemi causes soft-rot diseases of various plants by enzymatic degradation of the pectin in plant cell walls. Pectin is a complex polysaccharide. The main chain is constituted of galacturonate residues, and some of them are modified by methyl and/or acetyl esterification. Esterases are necessary to remove these modifications and, thus, to facilitate the further degradation of the polysaccharidic chain. In addition to PaeY, the first pectin acetylesterase identified in the E. chrysanthemi strain 3937, we showed that this bacterium produces a second pectin acetylesterase encoded by the gene paeX. The paeX open reading frame encodes a 322-residue precursor protein of 34,940 Da, including a 21-amino-acid signal peptide. Analysis of paeX transcription, by using gene fusions, revealed that it is induced by pectic catabolic products and affected by catabolite repression. The expression of paeX is regulated by the repressor KdgR, which controls all the steps of pectin catabolism; by the repressor PecS, which controls most of the pectinase genes; and by catabolite regulatory protein, the global activator of sugar catabolism. The paeX gene is situated in a cluster of genes involved in the catabolism and transport of pectic oligomers. In induced conditions, the two contiguous genes kdgM, encoding an oligogalacturonate-specific porin, and paeX are both transcribed as an operon from a promoter proximal to kdgM, but transcription of paeX can also be uncoupled from that of kdgM in noninduced conditions. PaeX is homologous to the C-terminal domain of the Butyrivibrio fibriosolvens xylanase XynB and to a few bacterial esterases. PaeX contains the typical box (GxSxG) corresponding to the active site of the large family of serine hydrolases. Purified PaeX releases acetate from various synthetic substrates and from sugar beet pectin. The PaeX activity increased after previous depolymerization and demethylation of pectin, indicating that its preferred substrates are nonmethylated oligogalacturonides. PaeX is mostly found in the periplasmic space of E. chrysanthemi. These data suggest that PaeX is mainly involved in the deacetylation of esterified oligogalacturonides that enter the periplasm by the KdgM porin.